2020
DOI: 10.1016/j.erss.2020.101544
|View full text |Cite
|
Sign up to set email alerts
|

Research on the social acceptance of renewable energy technologies: Past, present and future

Abstract: in 2007 [1] formalized what is still nowadays generally called the field of research on the social acceptance of renewable energy innovation or renewable energy technologies (RET). Twelve years later, we can say that this paper and associated proposal has been a landmark for research on this area, not only because it helped formalize it as a standalone field of research (see also [2,3]), but because it simultaneously provided a systematization of past research -the need to overcome the NIMBY (Not in my back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(94 citation statements)
references
References 85 publications
1
89
0
4
Order By: Relevance
“…The issue of social acceptance (SA) has been widely discussed in the context of renewable energy [86][87][88]. According to Wüstenhagen et al [87], SA is composed by three dimensions:…”
Section: Disadvantages Of Phspmentioning
confidence: 99%
“…The issue of social acceptance (SA) has been widely discussed in the context of renewable energy [86][87][88]. According to Wüstenhagen et al [87], SA is composed by three dimensions:…”
Section: Disadvantages Of Phspmentioning
confidence: 99%
“…On an individual micro level, local acceptance is dependent on individual factors like attitudes, landscape aesthetics, additional costs (benefits), knowledge and trust. Yet, conflicting structures and issues of acceptance are anchored at many levels, and as a whole go far beyond local resistance [131]. More recent research points to the connection between political and social acceptance on the one hand, and local acceptance on the other.…”
Section: Model Integrationmentioning
confidence: 99%
“…It was concluded that residents may accept renewable energy due to their concerns about environmental issues. [32] Presented three approaches of the social science research of renewable energy projects; these are normative, criticism, and critical approaches. [33] The authors say that framing discrepancies between the policy elites and residents represents a reflection of procedural injustice.…”
Section: Referencementioning
confidence: 99%